Antimalarial activity of solvent fractions of a leaf of Eucalyptus globulus labill against Plasmodium berghei infected mice - Mihret Ayalew; Seyfe Asrade Atnafie; Azmeraw Bekele (BMC, 2022)
Abstract Introduction The leaf of Eucalyptus globulus is commonly used in the traditional management of malaria. However, the efficacy of solvent fractions are didn't study yet scientifically. Thus, this study aimed to investigate the antimalarial efficacy of the solvent fractions of the leaf of Eucalyptus globulus in mice against P.berghei. Methods The antimalarial activity of the fractions was tested in a 4-day suppressive test, Rane's test, and prophylactic test models within P.berghei infected mice. The results were analyzed using a one-way analysis of variance (ANOVA) followed by a post hoc Tukey's test in version 20 SPSS. Results All fractions at all test doses in the three test models suppressed parasitemia (p < 0.001) compared to the negative controls. In addition, the CF and EA at all three test doses and the AF at 400 mg/kg in three antimalarial test models showed 50% and above parasitemia suppression. In compliance with this, all fractions at all test doses in all test models prolonged the mean survival time of the mice greater than 12 days, except the AF at a lower dose. All fractions at 400 mg/kg in the three test models prevented (p < 0.001) loss of body weight and rectal temperature compared to the negative controls. Furthermore, all fractions in all test models and doses prevented packed cell volume reduction (p < 0.05 to p < 0.001) compared to the negative controls.. Conclusion The findings of this study showed that CF and EAF had greater antimalarial activity compared to AF. This could be attributed to the presence of few phytochemicals in the AF in contrast to the CF and EAF. Overall, the results of this study further support the in vitro antimalarial activity study and the traditional use of the leaf in the management of malaria.